(untitled) (Revista Venezolana de Salud Pública, 2021)
Between April and June 2018, a cross-sectional study was conducted to determine the prevalence of evolutionary stages of intestinal parasites of medical interest in lettuces marketed at two free fairs and two supermarkets in the Caroní municipality, Bolívar state, Venezuela. A total of 95 samples were studied, having a homogeneous distribution regarding the place and city of sale. 91.6% (n = 87) of these samples presented contaminants and / or parasites of medical interest. Only in 20 samples (21.1%) were parasites of human identified. The most frequent of these was Blastocystis spp. (12.6%), with 10.6% in supermarkets and 14.6% at free fairs. Four different protozoan taxa followed, with the commensal amoebas Entamoeba coli (2.1%) and Endolimax nana (2.1%) being the most common. Within the helminths, both eggs (hookworm) and larva rhabditoides were found which were compatible according to their morphology with Strongyloides stercoralis (4 cases) and one with hookworm. When the contaminated lettuces are related according to the place of sale, no difference was found if the samples came from supermarkets (19.1%) or from free fairs (22.9%) (c2 (Yates Correction) = 0.20 df = 1; p > 0.05). Roman lettuce (37.5%) resulted more contamined by parasitic than the other types of lettuce considered (c2 = 8.19 df = 2; p <0.05). In conclusion, the presence of parasitic forms was demonstrated in samples of lettuce from supermarkets and free fairs in the Caroní municipality, Bolivar state, Venezuela.